Generative Artificial Intelligence in distance education: Transformations, challenges, and impact on academic integrity and student voice (Journal of Applied Learning and Teaching, 2024)
Generative artificial intelligence (GenAI) has reshaped distance education by prompting a shift towards student-centred initiatives to promote responsible AI usage. This study explores the transformative impact of GenAI in distance learning and focuses on academic integrity and student voices. This study uses the technology acceptance model to investigate how GenAI influences distance education. Three objectives guide the study: (1) exploring the transformative effects of GenAI in distance education, (2) understanding its impact on academic integrity, and (3) examining its influence on students’ academic voices in a South African open distance and e-learning university. Qualitative data was gathered through interviews with lecturers, open-ended evaluation questions with administrative staff, and focus group discussions with first-year students in an academic writing module. Findings highlight the need to bridge the gap between negative perceptions of AI’s impact on academic integrity and positive views on its potential to boost student confidence in learning. This research study aims to analyse GenAI’s role in distance education and provide insight into its potential, challenges, and strategies to ensure academic integrity and preserve students’ voices.